Features of investigation of murders committed using firearms - Husieva, V. O.; Гусєва, В. О.; Vlada Husieva (Scientific Journal of the National Academy of Internal Affairs. – 2021. – Vol. 26, No. 3. – P. 16-27, 2021)
Мета дослідження – визначити типові тактичні завдання, які необхідно виконати на початковому етапі розслідування вбивств, вчинених із застосуванням вогнепальної зброї, та особливості їх реалізації на основі аналізу слідчої та судової практики, а також досліджень українських та зарубіжних дослідників.

The purpose of the study is to determine the typical tactical tasks to be performed at the initial stage of investigation of murders committed using firearms, and the specific features of their implementation, based on the analysis of investigative and judicial practice, and studies of Ukrainian and foreign researchers. Methodology. The general dialectical and special research methods are used to achieve this goal, in particular: system analysis, comparative-legal, and system-structural methods. The scientific originality of the study lies in the fact that based on the analysis of available studies in the outlined area, materials of investigative and judicial practice, typical tactical tasks to be performed at the initial stage of the investigation of intentional murders committed using firearms are considered. Conclusions. The position, according to which the activity of investigating murders committed using firearms is characterised by a prominent level of complexity because during their it is necessary to perform a set of tactical tasks is justified. It is emphasised that such tasks include: establishing the identity of the victim, the nature of the event of a criminal offence, the place and time of committing a criminal offence, the method of committing a criminal offence; examining the crime weapon; establishing the identity of the criminal and the motives for committing a crime. It is stated that tactical tasks depend on the current investigative situation, aimed at checking or refuting investigative versions. The implementation of tactical tasks during the investigation is possible by conducting a complex of investigative (search), secret investigative (search) and procedural actions, and separate measures to ensure criminal proceedings. In the context of this study, the most effective actions that should be taken are proposed, and some of their possibilities are identified.

Цель исследования - определить типичные тактические задачи, которые необходимо выполнить на начальном этапе расследования убийств, совершенных с применением огнестрельного оружия, и особенности их реализации, на основе анализа следственной и судебной практики, а также исследований украинских и зарубежных исследователей.
Keywords: криміналістика; Україна; типові тактичні завдання; початковий етап розслідування; вбивство; розслідування вбивств; вбивства, вчинені із застосуванням вогнепальної зброї; вогнепальна зброя; intentional murder; firearms; pre-trial investigation; criminal proceedings; tactical task; досудебное расследование; убийство; огнестрельное оружие